Visual Analysis: Design Confusion Of Canned Alcoholic Beverages Amongst Muslim Consumers In Malaysia - Abdul Aziz, Mohd Nasiruddin; Daimin, Ghazali; Ahmad, Ahmad Khairul Azizi (2016)

(untitled)
Packaging design plays an important role to attract buyers. Several cases have been reported on the unintentional buying of canned alcoholic beverages by Muslims caused by the confusing packaging design between the alcoholic and non-alcoholic beverages. Many studies on the development of packaging design for halal food products and halal beverages have been carried out. However, there is a lack of studies on alcoholic beverages in Malaysia because of the religious sensitivities in the matter of halal and haram. This research paper has aimed to define the confusing elements on alcoholic cans to help the Muslim consumers in recognising the canned alcoholic beverages effectively. A survey has been conducted to get the clarification from Muslim consumers on the confusing design elements. Based on the survey results, the visual analysis investigated the elements (pattern, colour, brand, images, and typography) to get the priority flow on how to recognise alcoholic beverages easily and effectively. The findings of the visual analysis are discussed in terms of the similarities in the design element from the principal display panel (PDP) of the cans